The celebration of the indigenous culture and identity in waiting for the Mahatma - Mohammad Ayub Jajja (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Postcolonial writers reject the colonialist ideology of superiority and containment, disassociate themselves from cultural imperialism and celebrate the indigenous culture and identity in all forms and shapes, to assert the native identity and culture. They also touch upon the issues of mimicry, assimilation and hybridity experienced by the native cultures and people. R.K. Narayan in Waiting for the Mahatma has dealt with all these aspects of the postcolonial writings. The present study intended to investigate the portrayal of the celebration of the indigenous culture and identity by Narayan in Waiting for the Mahatma, in the light of postcolonial critical theory. The study found that Narayan has celebrated the Indian culture, traditions, identity and above all the status and stature of Gandhi as Mahatma in the novel, thereby, reinforcing his credentials as a postcolonial writer.
Keywords: 330; celebration of indigenous; mimicry; identity; oppression; hybridity; colonialist ideology